2005
DOI: 10.1385/ncc:3:2:132
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Implications of Diastolic Dysfunction After Subarachnoid Hemorrhage

Abstract: Diastolic dysfunction is common after SAH. It is associated with history of hypertension and older age and may explain the development of pulmonary edema in many SAH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
30
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 59 publications
6
30
0
Order By: Relevance
“…Consistent with the paper of Kopelnik et al [37], 28% of patients had regional wall motion score more than 1 on at least 1 study day, suggesting RWMA [4]. In addition, 15% of patients were characterized by impaired global systolic function (LVEF < 50%).…”
Section: Subarachnoid Hemorrhage and Cardiac Dysfunctionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with the paper of Kopelnik et al [37], 28% of patients had regional wall motion score more than 1 on at least 1 study day, suggesting RWMA [4]. In addition, 15% of patients were characterized by impaired global systolic function (LVEF < 50%).…”
Section: Subarachnoid Hemorrhage and Cardiac Dysfunctionsupporting
confidence: 86%
“…Never theless, prevalence of diastolic dysfunction reached 71% of all SAH subjects (impaired relaxation, pseudonormal, restrictive pattern) and was associated with older age and history of hypertension [37]. As proven by Kopelnik et al [37], diastolic dysfunction predisposed patients to pulmonary edema, while systolic dysfunction was considerably less frequent in this clinical scenario.…”
Section: Subarachnoid Hemorrhage and Cardiac Dysfunctionmentioning
confidence: 91%
See 1 more Smart Citation
“…SAH is frequently associated with changes in cardiac physiology, including left ventricular diastolic dysfunction, electrocardiac aberrancies, and in rare cases takotsubo cardiomyopathy [9,10]. Following administration of inotropic agents for HHH therapy, a small proportion of patients fail to respond due to underlying or induced left ventricular outflow tract (LVOT) obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…The most common abnormalities (prolonged QT-interval, ST-T changes, pathological T-waves, and U-waves) have been shown to occur in 27 to 100% of patients (1,2). Echocardiographic studies have shown abnormal left ventricular (LV) wall motion (13Á27%), which seems to be reversible (3Á7), and diastolic dysfunction (71%) (8). Others have reported myocardial necrosis measured by CK-MB and troponin I and T (3,7,9), and subendocardial necrosis and haemorrhages have been described at autopsy (10).…”
mentioning
confidence: 99%